2018
DOI: 10.1177/0021909618811838
|View full text |Cite
|
Sign up to set email alerts
|

Political Ecology and Contours of Vulnerability to Water Insecurity in Semiarid North-Eastern Ghana

Abstract: Vulnerability to water insecurity in Ghana has often been characterised as a biophysical phenomenon that can be objectively solved using technical and rational approaches to manage water resources use and allocation – thus, making vulnerability to water security discourse politically neutral. Contesting this orthodoxy, this article shows the multiple mechanisms and structures that undergird vulnerability of households to water insecurity in semiarid Ghana. Vulnerability to water insecurity is often veiled in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…They are therefore important determinants of socio-health vulnerabilities. Regarding access to water, this refers to "political ecology" which " recognizes that access and control over resources , including water , are rooted in local stories and social relations " [ 126 , 127 ]. Indeed, our interviews reveal that the notions of territory, marginality, and social exclusion shape the landscape of water resources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are therefore important determinants of socio-health vulnerabilities. Regarding access to water, this refers to "political ecology" which " recognizes that access and control over resources , including water , are rooted in local stories and social relations " [ 126 , 127 ]. Indeed, our interviews reveal that the notions of territory, marginality, and social exclusion shape the landscape of water resources.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly the case for marginal populations such as the Fulani [ 128 , 129 ]. These socially constructed and politically imposed inequalities lead to an unequal distribution of access and use of water and health care, as Dinko et al [ 126 ] has shown in Ghana.…”
Section: Discussionmentioning
confidence: 99%
“…Even when sufficient water is physically available, water may still be inaccessible (Akinyemi et al, 2005; Alexander et al, 2015; Armah et al, 2018; Asoba et al, 2019; Atangana Ondoa, 2017; Busari, 2002; Cole et al, 2015; Debela et al, 2020; Dinko et al, 2018; Dugard & Mohlakoan, 2009; Dungumaro, 2007; Emenike et al, 2017; Engel et al, 2007; Fisher et al, 2015; Foster, 2013; Gondo & Kolawole, 2013; Hamlet et al, 2021; Hope et al, 2020; Hope & Rouse, 2013; Marcatelli, 2013; Marcatelli, 2014; Marson & Savin, 2014; Miller, Frongillo, et al, 2021; Mosimane & Kamwi, 2020; et al, 2006; Sjöstedt, 2009; Smiley et al, 2020; Swatuk & Kgomotso, 2007; Yang et al, 2013). Economic water scarcity is defined as a lack of infrastructure or poor water resources management (Busari, 2002; Noemdoe et al, 2006; Swatuk & Kgomotso, 2007), and is a factor in SSA that increases distance required to fetch water (Egbinola, 2017).…”
Section: Results—climate Change Water and Women: Complex Interlinkagesmentioning
confidence: 99%
“…Dinko's dissertation study aims at understanding the dynamics and lived experience of climate-induced water insecurity at the local level in Ghana's Sudan Savannah. The Sudan Savannah is the driest climate in Ghana with a distinctly short rainfall season followed by a prolonged period of drought (Dinko, Yaro, & Kusimi, 2019;Wossen & Berger, 2015). With livelihoods almost entirely dependent on agriculture and the natural environment, Ghanaians need access to irrigation water in order to survive the nine-month dry season.…”
Section: The Benefits Of Interdisciplinary Methods In Water Security ...mentioning
confidence: 99%